Acupuncture for Osteoporosis: a Review of Its Clinical and Preclinical Studies - Yimiao Tian; Lili Wang; Tianshu Xu; Rui Li; Ruyuan Zhu; Beibei Chen; Hao Zhang; Bingke Xia; Yiwen Che; Dandan Zhao; Dongwei Zhang (Medical Association of Pharmacopuncture Institute, 2022)
Acupuncture has gained growing attention in the management of osteoporosis (OP). However, a comprehensive review has not yet been conducted on the efficacy and challenges of acupuncture in preliminary research and clinical trials. Therefore, an extensive literature search was conducted using electronic databases, including PubMed (www.ncbi.nlm.nih.gov/pubmed), CNKI (www.cnki.net), and Web of Science, for studies published from the beginning of 2000 to the end of May 2022. Combinations of synonyms for OP, acupuncture, traditional Chinese medicine, clinical trial, preclinical study, and animal experiments were searched. A total of 290 papers were consulted, including 115 reviews, 109 clinical observations, and 66 preclinical studies. There is accumulating evidence to support the beneficial role of acupuncture in preserving bone quality and relieving clinical symptoms based on clinical and preclinical investigations. The top ten most commonly used acupoints are BL23, ST36, BL20, BL11, CV4, GV4, SP 6, KI3, BL18, and GB39. The underlying mechanisms behind the benefits of acupuncture may be linked with the regulation of the hypothalamic-pituitary-gonadal (adrenal) axis and activation of the Wnt/β-catenin and OPG/RANKL/RANK signaling pathways. In summary, strong evidence may still come from prospective and well-designed clinical trials to shed light on the potential role of acupuncture in preserving bone loss. Future investigations are needed to explore the potential underlying mechanisms, long-term clinical efficacy, and compliance of acupuncture in OP management.